Recent Advances in Doppler Signal Processing and Modelling Techniques for Fetal Monitoring - Yoshitaka Kimura (Frontiers Research Topics, 2018)
The guest editors of this eBook have accepted 10 very high-quality submissions for inclusion in a special issue of Frontiers in Physiology. The key difference between this eBook and contemporary fetal physiology related literature is that this Research Topic summarizes additional insights into the physiological link between physiologically understandable mathematical indices of fetal signals and the developing cardiovascular functions in fetal health and compromises. This book should be of considerable help to researchers, professionals in fetal monitoring device industries, academics, and graduate students from a wide range of disciplines. The text provides a comprehensive account of recent research in this emerging field and we anticipate that the concepts presented here will generate further research in this field.